Multiparameter ranking of carbazoles for anti-trypanosome lead discovery - Sharma, Amrita; Sanz-Rodriguez, Carlos E.; Pollastri, Michael P.; Purmal, Andrei; Mensa-Wilmot, Kojo (Frontiers in Drug Discovery, 2024)
Criteria for progression of hits in discovery of leads for Human African trypanosomiasis (HAT), a neglected disease caused by the microbial eukaryote Trypanosoma brucei, are not standardized. Hits are advanced upon meeting thresholds for drug-like molecules. Following those principles pharmacokinetics (Cmax and AUC0-6h) and anti-trypanosome characteristics predicted arrest of T. brucei proliferation in mice by three curaxins. Unexpectedly, while CBL0137 cured HAT in a mouse model, CBL0174 and CBL0187, structure analogs of CBL0137 with similar drug-like properties failed to control division of T. brucei. Herein, we propose an alternative strategy that integrates physicochemical, metabolic, pharmacokinetic, pharmacodynamic, tissue distribution and trypanocidality parameters into calculation of a score for ranking compounds in hit-to-lead campaigns. Data from our studies of curaxins support feasibility of the goal. Serum dropped anti-trypanosome potency of CBL0174 and CBL0187 considerably. Delayed trypanocidal concentrations (DTC25 and DTC90) were used to study modes of curaxin actions in trypanosomes. Efficacy of CBL0137 in mice correlated with (i) high AUC0-6h:DTC90 ratio, (ii) blocking of transferrin endocytosis, and (iii) inhibition of protein synthesis. Hydroxylation of the carbazole prevented CBL0137 from inhibiting endocytosis of Tf. A multiparametric score termed "Curaxin HAT Lead Efficacy (CHLE)" was calculated using pharmacokinetic, physicochemical, metabolism, brain exposure, and pharmacodynamic data; CBL0137 was the highest scoring hit. Complementing these observations, and predictive of performance of curaxins in mice, CBL0137, but not CBL0174 or CBL0187, was trypanocidal after exposure of trypanosomes to AUC0-6h amounts of the hits for six hours in vitro. We discuss a role for CHLE scores in ranking of curaxins for anti-HAT lead discovery. Principles used to develop CHLE scores may be used to calculate new ones for other scaffolds during discovery of leads for HAT or other infectious diseases.